“It Is Not Out There, and It’s in Here”: The Challengingand Duality Perspective of Teaching Gender in Journalism and Media Studies in Private Universities - Angeliqa, Fitria; Nurhajati, Lestari (UI Scholars Hub, 2022)
This study aimed to determine challenges of teaching gender in journalism and media studies courses on various campuses in Jakarta, Indonesia. The ‘otherness’ is still ghosting the lecturer, where the duality is a must to create comprehension on gender topics. It is essential because teaching the gender issue in communication study programs in Indonesia does not reflect a lot on women’s experiences. The theory of gender pedagogy is the basis of this study. Meanwhile, the duality perspective serves as its framework. Gender pedagogy is not just a tool, strategy, or practical technique for understanding gender teaching in education. Teaching gender equality values in the classroom becomes a challenge for teachers. This research applied a qualitative approach and hermeneutic phenomenology strategy. The research used in-depth interviews for research instruments. This research indicated various levels of understanding and implementation of teaching gender issues. Even in some universities that do not include gender issues in journalism and media studies courses, the lecturers must struggle to fit gender issues in various teaching opportunities in their classrooms. Penelitian ini bertujuan untuk mengetahui tantangan pengajaran gender dalam mata kuliah jurnalisme dan studi media di berbagai kampus di Jakarta, Indonesia. ‘Keberbedaan’ masih mengaburkan pengajaran, di mana dualitas menjadi suatu keharusan untuk menciptakan pemahaman tentang topik gender. Hal ini penting karena pengajaran isu gender di program studi komunikasi di Indonesia tidak banyak merefleksikan pengalaman perempuan. Teori pedagogi gender adalah dasar dari penelitian ini. Sementara itu, perspektif dualitas berfungsi sebagai kerangka kerjanya. Pedagogi gender bukan hanya alat, strategi, atau teknik praktis untuk memahami pengajaran gender dalam pendidikan. Mengajarkan nilai-nilai kesetaraan gender di kelas menjadi tantangan tersendiri bagi guru. Penelitian ini menerapkan pendekatan kualitatif dan strategi fenomenologi hermeneutika. Penelitian ini menggunakan wawancara mendalam untuk instrumen penelitian. Penelitian ini menunjukkan berbagai tingkat pemahaman dan implementasi pengajaran isu gender. Bahkan di beberapa universitas yang tidak memasukkan isu gender dalam mata kuliah jurnalisme dan studi media, para dosen harus berjuang untuk menyesuaikan isu gender dalam berbagai kesempatan mengajar di kelas mereka.